Pengaruh Stres Guru Terhadap Teacher Well-Being Pada Guru Yang Mengajar Di Sekolah Dasar Inklusi - Fitri Lestari Issom; Fachrurozzy (Journal of Research and Measurement in Psychology: JPPP, 2022)
This research aims to find effects of teachers’ stress on teacher well-being in teachers of inclusive elementary schools. This is a quantitative research with one predictor linear regression analysis. Samples in this research were 117 inclusive elementary schools collected using the accidental sampling. Variable of teachers’ stress was measured using Teacher Stress Inventory (TSI) developed by Collie and variable of teacher well-being was measured using Teacher Well-Being Scale (TWBS) developed by Firman & Fastenau. The research results showed significance value (ρ) OG 0.000, which was smaller than 0.5, and it was found that F-count was 29.795 and F-table was 3.92. It meant that teachers’ stress provided significant effects on teacher well-being in teachers of inclusive elementary schools. This study concluded that if teachers experience high levels of stress, it will reduce their level of teacher well-being. In addition, it was found that R-square was 0.206, which meant that teachers’ stress provided effect of 20.6% on teacher well-being in teachers of inclusive elementary schools.